PENGARUH ENDORSEMENT FASHION, MEDIA SOSIAL INSTAGRAM DAN LOKASI TOKO TERHADAP MINAT BELI PAKAIAN REMAJA (Studi Kasus Toko Duta Tanah Abang Kota Bengkulu) - Renaldi Adam Makna; Yulius Wahyu Setiadi ((JEMS) Jurnal Entrepreneur dan Manajemen Sains, 2022)
This study aims to determine the Effect of Endorsement Fashion, Instagram Social Media and Store Locations on Teenagers' Interest in Buying Clothing. This type of research uses quantitative methods, the object of this research is the Consumers of Duta Tanah Abang Stores in Bengkulu City with a sampling method that is accidental sampling technique. The number of respondents in this study were 97 people. In this research, the author uses data collection methods by means of observation, interviews and distributing questionnaires or questionnaires. By using data analysis techniques using Instrument Test, namely Validity Test and Reliability Test, Classical Assumption Test, namely Multicollinearity Test, Normality Test. and Heteroscedasticity Test, Multiple Linear Regression Analysis Test, Coefficient of Determination (R2), and Hypothesis Testing, namely t-test and f-test. The results of this study can be concluded that the Endorsement Fashion variable has a partially significant effect on the Interest in Buying Teen Clothing at the Tanah Abang Store in Bengkulu City, Social Media Instagram has a partially significant effect on the Interest in Buying Teen Clothing at the Tanah Abang Store in Bengkulu City, the Store Location has a partially significant effect. on the Interest in Buying Teen Clothing at the Tanah Abang Store in Bengkulu City, and Endorsement Fashion, Instagram Social Media and Store Location have a significant simultaneous effect on the Interest in Buying Teen Clothing at the Tanah Abang Store in Bengkulu City. Keywords : Endorsement Fashion, Instagram Social Media and Store Location, Buying Interest